Hot and Heterogenous High‐3He/4He Components: New Constraints From Proto‐Iceland Plume Lavas From Baffin Island. (10th December 2019) - Willhite, Lori N.; Jackson, Matthew G.; Blichert‐Toft, Janne; Bindeman, Ilya; Kurz, Mark D.; Halldórsson, Sæmundur A.; Harðardóttir, Sunna; Gazel, Esteban; Price, Allison A.; Byerly, Benjamin L.
Abstract: The Icelandic hotspot has erupted basaltic magma with the highest mantle‐derived 3 He/ 4 He over a period spanning much of the Cenozoic, from the early‐Cenozoic Baffin Island‐West Greenland flood basalt province (49.8 R A ), to mid‐Miocene lavas in northwest Iceland (40.2 to 47.5 R A ), to Pleistocene lavas in Iceland's neovolcanic zone (34.3 R A ). The Baffin Island lavas transited through and potentially assimilated variable amounts of Precambrian continental basement. We use geochemical indicators sensitive to continental crust assimilation (Nb/Th, Ce/Pb, MgO) to identify the least crustally contaminated lavas. Four lavas, identified as "least crustally contaminated, " have high MgO (>15 wt.%), and Nb/Th and Ce/Pb that fall within the mantle range (Nb/Th = 15.6 ± 2.6, Ce/Pb = 24.3 ± 4.3). These lavas have 87 Sr/ 86 Sr = 0.703008–0.703021, 143 Nd/ 144 Nd = 0.513094–0.513128, 176 Hf/ 177 Hf = 0.283265–0.283284, 206 Pb/ 204 Pb = 17.7560–17.9375, 3 He/ 4 He up to 39.9 R A, and mantle‐like δ 18 O of 5.03–5.21‰. The radiogenic isotopic compositions of the least crustally contaminated lavas are more geochemically depleted than Iceland high‐ 3 He/ 4 He lavas, a shift that cannot be explained by continental crust assimilation in the Baffin suite. Thus, we argue for the presence of two geochemically distinct high‐ 3 He/ 4 He components within the Iceland plume. Additionally, the least crustally contaminated primary melts from Baffin Island‐West Greenland have higher mantle potential temperatures (1510 to 1630 °C) than Siqueiros mid‐ocean ridge basalts (1300 to 1410 °C), which attests to a hot, buoyant plume origin for early Iceland plume lavas. These observations support the contention that the geochemically heterogeneous high‐ 3 He/ 4 He domain is dense, located in the deep mantle, and sampled by only the hottest plumes. Key Points: Baffin Island‐West Greenland high‐ 3 He/ 4 He lavas are more geochemically depleted than any other high‐ 3 He/ 4 He lavas globally The isotopic composition of the high‐ 3 He/ 4 He mantle source in the Iceland plume has evolved through time Baffin Island and West Greenland primary melts record hotter temperatures than high‐MgO MORB, consistent with a deep, dense plume source